Inventory of fruit trees along the Duyoh-Jagoi trail, Tibawang Raya and Tibawang Sauh of Gunung Jagoi community forest - Eline, Iran (Universiti Malaysia Sarawak (UNIMAS), 2012)
Kampung Jagoi which is located at Gunung Jagoi Bau, Sarawak is an ancestral village for JagoiBidayuh people. Living at high altitude makes fruit trees as their sources of foods. The objectives of this study are to determine the diversity of fruit trees at the old orchards and the main trail of community forest of Gunung Jagoi and to study the distribution pattern of fruit trees species along the trail and the old orchards. The diversity of fruit trees planted by past generation along the main trail and the two old fruit orchards at Gunung Jagoi community forest was accessed. Plot sampling was carried out at the old fruit orchards (Tibawang Raya and Tibawang Sauh) and along the trail. A total of 102 fruit trees from 20 species and 11 families were recorded. The Shannon’s diversity index for the fruit trees along the trail and at the old orchards are 1.793 and 2.244 respectively. Artocarpus integer was the most abundance fruit trees recorded followed by Baccaurea macrocarpa, Lansium domesticum and Durio zibethinus. Distribution pattern of fruit trees counted is evenly distributed at the old orchards and skewed to sub-plot 1 along the main trail.